Preparative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols using silver nitrate-impregnated silica gel medium pressure liquid chromatography and analysis of sandalwood oil - Daramwar, Pankaj P.; Srivastava, Prabhakar Lal; Priyadarshini, Balaraman; Thulasiram, Hirekodathakallu V. (Analyst, 2012)
The major sesquiterpene constituents of East-Indian sandalwood oil (Z)-alpha- and (Z)-beta-santalols have shown to be responsible for most of the biological activities and organoleptic properties of sandalwood oil. The work reported here describes the strategic use of medium pressure liquid chromatography (MPLC) for the separation of both alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols. Silver nitrate impregnated silica gel was used as the stationary phase in MPLC for quantitative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols with mobile phases hexane and dichloromethane, respectively. The purities of alpha-santalene and (Z)-alpha-santalol obtained were >96%; however, beta-santalene and (Z)-beta-santalol were obtained with their respective inseparable epi-isomers. Limits of quantification (LoQ) relative to the FID detector were measured for important sesquiterpene alcohols of heartwood oil of S. album using serial dilutions of the standard stock solutions and demonstrated that the quality of the commercial sandalwood oil can be assessed for the content of individual sesquiterpene alcohols regulated by Australian Standard (AS2112-2003), International Organization for Standardization ISO 3518: 2002 (E) and European Union (E. U.).

Fungi mediated production and practical purification of (R)-(-)-3-quinuclidinol - Kolet, Swati P.; Jadhav, Dipesh D.; Priyadarshini, Balaraman; Swarge, Bhagyashree N.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
A fungal system belonging to Mucoraceae family (Mucor piriformis) was explored for the asymmetric reduction of a prochiral ketone, 3-quinuclidinone (I) in an efficient manner to produce an important pharmaceutical precursor (R)-(-)-3-quinuclidinol (II) with similar to 96% enantiomeric excess. The efficiency of the process was improved by developing a cation exchange resin (Amberlite IR-120) which assisted the purification of water soluble metabolite II from fermentation media. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R)-(-)-3-Quinuclidinol; Amberlite IR-120; Biotransformation; Ion exchange resin; Mucor pinformis